2021
DOI: 10.4236/as.2021.1212090
|View full text |Cite
|
Sign up to set email alerts
|

<i>Cannabis sativa</i> L. Response to Narrow Bandwidth UV and the Combination of Blue and Red Light during the Final Stages of Flowering on Leaf Level Gas-Exchange Parameters, Secondary Metabolite Production, and Yield

Abstract: Many modifications to growing environments and specific stress induction techniques exist which are supported by preliminary research to increase yield and/or concentration of secondary metabolites in Cannabis sativa L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In another study, it was also observed that there was no effect in phytocannabinoid concentration and inflorescence yield in the genotype 'Meridian' (high THC content) with supplemental UV-A spectra [84]. However, Jenkins (2021) [85] observed a 4.1% increase in the THC concentration in two genotypes ('Larry OG' and 'Super White') and no changes in another genotype ('Pootie Tang'). The UV supplementation decreased the inflorescence yield of 'Larry OG' [85].…”
Section: Effects Of Lightmentioning
confidence: 94%
See 2 more Smart Citations
“…In another study, it was also observed that there was no effect in phytocannabinoid concentration and inflorescence yield in the genotype 'Meridian' (high THC content) with supplemental UV-A spectra [84]. However, Jenkins (2021) [85] observed a 4.1% increase in the THC concentration in two genotypes ('Larry OG' and 'Super White') and no changes in another genotype ('Pootie Tang'). The UV supplementation decreased the inflorescence yield of 'Larry OG' [85].…”
Section: Effects Of Lightmentioning
confidence: 94%
“…In contrast, the concentrations of other phytocannabinoids (such as THCA, CDBA, and CBCA) decreased by up to 40% under LED culturing, exhibiting a specific metabolite response to light spectra and a potential for the inhibition of enzymatic activity under LED light [80]. Another study found a 2.5% increase in THC content in plants supplemented with LED light with a blue and redder spectrum [85]. However, this variation in THC production may have been caused by the higher light intensity compared to the control treatment.…”
Section: Effects Of Lightmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, the horticultural industry looks for cost reduction not only to grow food but also medicinal cannabis, the demands on light of which can be even seven times larger than in the case of crops. There are multiple studies that elaborate on various photosynthesis mechanisms in order to increase the overall cost-effectiveness and the plants' growth rate [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…1 ; Runge et al 1996 ; Dietzel et al 2008 ; Scheibe and Dietz 2012 ; Kim and Apel 2013 ; Sheerin and Hiltbrunner 2017 ; Gasperl et al 2021 ). LEDs have gained more and more importance as energy-efficient plant growth light sources during the last years and have been used to study the involvement of light, with special focus on red and blue spectra, in the regulation of growth and development of the model plant Arabidopsis thaliana and various crop plants; in this context, the enhanced accumulation of specific metabolites is also of great interest (Li et al 2017 ; Monostori et al 2018 ; Kong and Zheng 2020 ; Jenkins 2021 ; Samuolienė et al 2020 ; Appolloni et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%